Malthus Meets Luther: The Economics Behind the German Reformation - Malik Curuk; Sjak Smulders (Center for Economic Studies and ifo Institute (CESifo), 2016)
The Reformation provided a powerful source of legitimacy for secularization of governance and enabled the regional authorities to change the institutional structure to eliminate the inefficiencies under the prevailing (Catholic) regime. We investigate this idea in a simple model of regime change and show that the regions where the prevailing institutions are less appropriate, i.e. poorer regions with greater economic potential, should have been more likely to adopt the Reformation. Using detailed data on religious denominations, city characteristics and exogenous measures of agricultural potential, we empirically confirm this hypothesis for the cities in the 16th century Holy Roman Empire. This finding points to an economic rationale of the adoption of Protestantism as a vehicle of institutional change.
Keywords: D72; N33; N43; N53; Z12; 330; institutional change; appropriate institutions; Malthusian growth; economics of religion; German Reformation; regional autonomy; agricultural potential; urbanization